The UK’s Research Information Infrastructure: Key Issues and Challenges - Jubb, Michael (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Producing, disseminating, and using information is at the heart of any research and innovation system. Like other countries in Europe, the UK faces a number of challenges in seeking to develop an efficient infrastructure of information services to meet the needs and expectations of researchers who are exploiting new ways of operating and communicating with each other. This paper is based on a presentation made at the LIBER annual conference in Uppsala in July 2006, and sets out some of the key challenges, and the role of the Research Information Network ( RIN) in seeking to address them.